Necrotising fasciitis of the lower limb due to perforated inguinal hernia - Georgiev Hristov, Tihomir; Álvarez Gallego, M.; Juliá, J. B.; Redondo, M. G.; Verón, A.; Castell Gómez, J. T. (My University, 2010)
Acute inguinal hernia complications (incarceration, strangulation) are relatively frequent conditions, especially in the elderly. Urgent surgery is the appropriate treatment if manual reduction is not achieved or strangulation or perforation is suspected. We present a 77-year-old patient with necrotising fasciitis of the lower limb as a consequence of extraperitoneal perforation of a sliding inguinal hernia. This devastating condition was diagnosed 20 h after the manual reduction of the hernia. Suspicion arose at the physical examination (crepitation, signs of cellulitis) and clinical deterioration of the patient, and was confirmed by computed tomography (CT) scanning. Urgent surgery was performed, including sigmoidectomy, debridement of the necrotic tissues of the medial and anterior thigh compartment, and fasciectomy, combined with optimal intensive care support. No signs of peritoneal or pelvic involvement were found. However, the comorbidities, advanced age and the progression of the disease led to fatal outcome. Early recognition of the complications of strangulated hernias is of vital importance for successful treatment in these cases, even if no signs of acute abdomen are present.